Peningkatan Kompetensi Komunikasi dan Negosiasi Sumber Daya Manusia Berbasis Digital Marketing bagi Masyarakat Pondok Petir - Edy Fajar Prasetyo; Fadhel Kusuma; Muhamad Irfan Hakim; Rikar Azka; Tri Maulana (Universitas 17 Agustus 1945 Semarang, 2025)
The digital era has significantly transformed the business landscape, making digital-based communication and negotiation skills essential for human resources (HR) to enhance their competitiveness in the global market. This study aims to analyze the effectiveness of a digital marketing-based communication and negotiation competency enhancement program for the community and MSME actors in Pondok Petir Village, Bojongsari District, Depok City. Using a descriptive qualitative approach with a participatory training method, this research evaluates the training's impact through pre-tests, post-tests, and participant feedback analysis. The findings indicate that the training significantly contributes to improving participants' digital skills, expanding access to technology-based training, and strengthening their business competitiveness. Furthermore, collaboration with various stakeholders, creativity in digital marketing, and sustainable strategies play a crucial role in ensuring the long-term effectiveness of the program. However, challenges such as limited internet access and resistance to change remain major obstacles to program implementation. Therefore, this study recommends the development of sustainable training strategies, increased digital literacy, and active involvement of the government and community in supporting the enhancement of digital-based human resources at the local level.